10.28932 Perancangan Dashboard Visualisasi Data untuk Analisis Performa Pemesanan Hotel TripVerse - Elroy Matthew Wiyanto (Universitas Kristen Maranatha, 2026)
The rapid growth of online hotel booking platforms generates a large volume of transactional data that can be utilized to support business performance analysis. However, such data are often not presented in a structured and easily interpretable form. This study aims to design and implement an admin dashboard based on data visualization to support hotel booking performance analysis. The dashboard presents key performance indicators, including Occupancy Rate, Average Length of Stay (ALOS), and Revenue per Available Room (RevPAR), through graphical and statistical summaries. The research method consists of requirement analysis, system design using Unified Modeling Language (UML), web-based dashboard implementation, and functional testing using the black box testing method. The results indicate that all dashboard features function properly and are able to consistently display hotel booking performance data based on selected time periods. The developed dashboard is expected to assist administrators in monitoring performance and making data-driven decisions more effectively.